Humor dan Covid-19: Makna Pesan dalam Akun Instagram @t_faturohman - Santi Susanti; Tine Silvana Rahmawati (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
Humor can be used to convey messages, one of which is about COVID-19. Using humor in conveying messages of COVID-19 is done by one of the humor writers in Bandung, Taufik Faturohman, through his Instagram account @t_faturohman. Messages posted on the account are writes in Sundanese. The choice of Sundanese language and humor in conveying messages is conducted to make messages easier to receive, and the receivers feel entertained. In addition, the use of Sundanese language remains sustainable. This study analyses messages related to COVID-19 on the @t_faturohman Instagram account, using Roland Barthes' semiotic analysis. The method used is qualitative with data collection techniques through text observation and library source enrichment. The object of his research is posts related to COVID-19. Data analysis used the Miles and Huberman analysis techniques. The results show that behind the humorous style conveyed there is an informative and educational meaning in the messages on the @t_faturohman account related to COVID-19